Development of a Green Chemistry E-Module Integrated with Ethno-STEAM for Enhancing Senior High School Students’ Environmental Conservation Skills - Epinur; Fuldiaratman; Nelyahardi; Hendra; Minarni (Jurnal Penelitian Pendidikan IPA, 2026)
This study developed and validated an Ethno-STEAM integrated e-module to enhance students’ conservation skills using the ADDIE model (Analysis, Design, Development, Implementation, and Evaluation). Data were collected through observations, interviews, and questionnaires. Expert validation results showed average scores of 4.6 for content, 4.875 for design, and 4.5 for practitioners, categorized as “very good” (interval 4.21–5.00). These findings confirm the feasibility of the e-module in terms of content quality, presentation, language, and design without significant revisions. Implementation results demonstrated notable improvements in students’ science literacy. Prior to the intervention, students were distributed at level 1 (23.40%), level 2 (50%), and level 3 (26.60%), with no students reaching levels 4 or 5. After implementation, the distribution shifted to level 1 (7.40%), level 2 (10%), level 3 (40%), level 4 (36.70%), and level 5 (5.90%). The novelty of this research lies in integrating Ethno-STEAM with local wisdom, which not only improves science literacy but also fosters conservation values such as appreciation, pride, and care for local culture. The e-module is therefore recommended as an effective, scientific, and character-oriented medium for chemistry learning.